2012
DOI: 10.3928/01477447-20120725-18
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of Treatment Using a Clavicular Hook Plate Versus a T-plate in Neer Type II Distal Clavicle Fractures

Abstract: AO clavicular hook plate fixation provides more rigid fixation and good bony union rates for Neer type II distal clavicular fractures. However, the hook may cause rotator cuff tears and subacromial impingement, which adversely affect the clinical results. T-plate fixation is another surgical method of treatment for unstable clavicle fractures, and its clinical efficacy has been demonstrated. The purpose of this study was to compare the clinical outcomes of AO clavicular hook plate and T-plate fixation for Neer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 31 publications
1
60
0
1
Order By: Relevance
“…It is therefore important to exercise caution when using hook plate [6][7][8][9][10][11][12][13]. In a recent study, Tan et al [26] reported 74 % of patients in the hook plate group had mild to severe shoulder pain. Kashii et al [8] observed one patient had acromial fracture, and hook cutout occurred in 19 of 34 patients who underwent hook plate fixation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore important to exercise caution when using hook plate [6][7][8][9][10][11][12][13]. In a recent study, Tan et al [26] reported 74 % of patients in the hook plate group had mild to severe shoulder pain. Kashii et al [8] observed one patient had acromial fracture, and hook cutout occurred in 19 of 34 patients who underwent hook plate fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported excellent results of distal clavicle fractures treated with locking plate [14,15,17,26,29,30]. Treatment for unstable distal clavicle fractures using a locking T-plate and a CC PDS (polydioxansulfate) cerclage can provide good and reliable clinical results and a 100 % union rate [16].…”
Section: Discussionmentioning
confidence: 99%
“…48e50 In other two level 3 studies hook plate was compared with distal radius plate and locking plate where hook plate seemed to have higher complication rate and resurgery rate for implant removal. 52,53 One level 2 study comparing hook plate with tension band wiring showed both the techniques to have comparable results. 55 Overall it seems that in spite of giving good functional outcome hook plate tend to produce major complications and there is a definite need for implant removal which again puts the patient under risk of one more general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,26e30 As already mentioned the one level 3 study which compared this implant with the hook plate showed it to have lesser complication and re-surgery rate. 52 Technically speaking there should be no need for implant removal as there is no breach into the AC joint. But hardware symptoms and implant failure can occur which needs an implant removal surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation